Synthesis of 2‐(N‐cyclicamino)quinoline combined with methyl (E)‐3‐(2/3/4‐aminophenyl)acrylates as potential antiparasitic agents. Issue 7 (12th March 2021) - Bokosi, Fostino R. B.; Beteck, Richard M.; Laming, Dustin; Hoppe, Heinrich C.; Tshiwawa, Tendamudzimu; Khanye, Setshaba D.
Abstract: A rationally designed series of 2‐( N ‐cyclicamino)quinolines coupled with methyl ( E )‐3‐(2/3/4‐aminophenyl)acrylates was synthesized and subjected to in vitro screening bioassays for potential antiplasmodial and antitrypanosomal activities against a chloroquine‐sensitive (3D7) strain of Plasmodium falciparum and nagana Trypanosoma brucei brucei 427, respectively. Substituent effects on activity were evaluated; meta ‐acrylate 24 and the ortho ‐acrylate 29 exhibited the highest antiplasmodial (IC50 = 1.4 µM) and antitrypanosomal (IC50 = 10.4 µM) activities, respectively. The activity against HeLa cells showed that the synthesized analogs are not cytotoxic at the maximum tested concentration. The ADME (absorption, distribution, metabolism, and excretion) drug‐like properties of the synthesized compounds were predicted through the SwissADME software. Abstract : A library of quinolines flagged at positions 2 and 3 by cyclic amines and amino phenylacrylates was synthesized and tested for their antiplasmodial and antitrypanosomal activities. The meta ‐acrylate compounds showed promising in vitro antiplasmodial activity against the chloroquine‐sensitive Plasmodium falciparum strain 3D7. All compounds showed no cytotoxicity against HeLa cells with viability greater than 85% at the concentration of 20 μM.